2022
DOI: 10.3390/ijerph191911868
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Shipping Emissions in Developing Country: A Case Study of Mohammad Bin Qasim Port, Pakistan

Abstract: Transportation has the highest dependence on fossil fuels of any sector and accounts for 37% of carbon dioxide (CO2) emissions. Maritime transportation is responsible for around 940 million tons of CO2 and approximately 3% of global emissions annually. The significant increase in shipping activities around the globe has magnified the generation of toxic pollutants. In recent years, shipping emissions have received significant attention in developed countries due to global climate change, while in developing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In recent years, CE has gained increasing attention in the face of climate deterioration [20][21][22]. Scholars have now conducted fruitful studies of CE around the world [23][24][25]. Moutinho et al [26] analyse the relevant factors driving CE changes in Europe and find that CE is closely linked to energy consumption and structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, CE has gained increasing attention in the face of climate deterioration [20][21][22]. Scholars have now conducted fruitful studies of CE around the world [23][24][25]. Moutinho et al [26] analyse the relevant factors driving CE changes in Europe and find that CE is closely linked to energy consumption and structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, the enhancement in accessibility is also reflected in the spatial compression, after the road networkhas been closed, and then the regional tourism traffic accessibility is significantly elevated and the spatial compression can be better reflected [48]. Another negative but noteworthy impact is that increased accessibility relies on the proliferation of road networks and increased traffic nodes, creating elevated consumption of fossil fuels, which can result in excessive pollutant emissions [49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Polluted saltwater accelerates corrosion, which speeds up the hull degradation of ships and submarines. Dockyard Laboratory found that mild steel loses 5.48 g/m2 per day in open saltwater, whereas Karachi Harbor loses 9.20 g/m2 per day (Hussain, et al 2022). The researchers estimate that Karachi Harbor marine pollution shortens ships' lifespan by roughly 33 percent.Frequent breakdowns and flaws in ship machinery, equipment, saltwater pumps, and pipelines directly result from seawater's high corrosion rates.…”
Section: Effects Of Marine Pollution On Ships and Portmentioning
confidence: 99%